Co-Encapsulation of Chlorin e6 and Chemotherapeutic Drugs in a PEGylated Liposome Enhance the Efficacy of Tumor Treatment: Pharmacokinetics and Therapeutic Efficacy - Po-Chun Peng; Ruey-Long Hong; Tsuimin Tsai; Chin-Tin Chen (MDPI AG, 2019)
Long-circulating PEG-modified liposome has been shown to improve pharmacokinetic properties and reduce systemic toxicity in cancer treatment. However, drug bioavailability from liposome remains a major challenge to the improvement of its therapeutic efficacy. Previously, we designed a PEGylated dual-effect liposome (named as PL-Dox-Ce6) with chlorin e6 incorporated in the lipid bilayer and Doxorubicin encapsulated in the interior. In this study, another dual-effect liposome with cisplatin encapsulated in the interior was further developed. The pharmacokinetics of these two dual-effect liposomes were studied in tumor-bearing mice. Based on the kinetic data of tumor and plasma, light irradiation was applied onto the tumors at different time points after drug administration to compare the therapeutic efficacy. We demonstrated that a single dose of the dual-effect liposomes combined with two doses of light irradiation can completely eradicate over 90% of the tumor in mice alone with significant survival rate and no toxicity. Thus, this study established a platform that utilizes the dual-effect liposome which combines photodynamic therapy and chemotherapy to improve the therapeutic outcomes of tumors.